Uncommon Presentation of Osteochondroma in a Flat Bone of Left Iliac Blade Lesion: A Case Report - Sushant Sah; Sujan Sharma; Bishal Panthi; Govinda Bhandari; Aron Shrestha; Lalita Poudel Chhetri; Abhishek Kumar Thakur (Journal of Nepal Medical Association)
Osteochondromas are the most common benign bone tumors, frequently affecting the metaphysis of long bones. Their occurrence in flat bones is rare, accounting for only 5% of cases. This report presents a solitary osteochondroma of the iliac blade, a rare anatomical location. A 17-year-old male presented with a progressively enlarging, painless bony mass on the hip, associated with lower back pain. Imaging studies, including ultrasound and MRI, revealed a bony outgrowth with medullary and cortical continuity and a benign cartilage cap. The patient underwent en bloc excision biopsy under spinal anesthesia, removing the lesion along with a portion of the iliac crest. Osteochondromas in flat bones are rare, posing diagnostic challenges. While imaging provides critical diagnostic clues, histopathology remains essential for confirmation. Surgical excision is the treatment of choice for symptomatic cases. This case highlights the importance of recognizing osteochondromas in unusual locations and employing multidisciplinary approach for optimal diagnosis and management.